MOVING TOWARDS OBJECTIVE RESPONSIBILITY; FRANCE AND USA AS A CASE STUDY - Dr. Bakhit Mohd AlDajeh (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The previous doctrinal and legislative development was not enough to reach a fair system that would enable civil responsibility to keep pace with the changes of the times, and to ensure the provision of legal solutions to the new developments. After the industrial revolution and the great development of mechanical equipment and the intervention of technology in industries the number of unknown dangers has increase. The modern jurisprudence is seeking for advanced solutions that take away civil responsibility from the reality of the crisis facing, so the focus would be substantially on the idea of harm, without the search for fault act or not, as the idea of fault act was been decommissioned. The stage of the supposed fault act was the beginning of the path to the next stage to reach a responsibility based on fundamentally of the fault act. This research aims to shed light on objective civil liability, by clarifying its concept, definition and characteristics. The approach used in this study is considered the analytical approach, through the collection and analysis of information, reliance on critical analytical investigation and problem identification.